Tinjauan Yuridis Pembentukan Lembaga Penjaminan Polis Asuransi di Indonesia - Aria Sri Agustin; A.M Hasan Ali; Elviza Fauzia (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
The main problem in this thesis is regarding legal certainty and protection for insurance policy holders after the issuance of Article 53 paragraph (1) of the Insurance Law which mandates the establishment of an insurance policy guarantee institution in Indonesia. Since the issuance of this law since 2014 until now, the institution has not yet been formed. So that the problem of default cases experienced by many policyholders. This study aims to determine the legal protection of policyholders in countries that have implemented it. This research method uses a statutory approach, namely the related Law Number 40 of 2014 and compares it with the regulations regarding the Policy Guarantee Institution in Japan using a comparative approach. The results of this study indicate that the statutory regulations -The legislation regarding the Insurance Policy Guarantee Agency in Japan is very adequate due to the management and preventive and repressive measures for default insurance. So that the Indonesian State needs to implement it in order to provide legal protection for every insurance policy holder in Indonesia.Keywords: Insurance, Policy Guarantee Institution, Insurance Claims